STUDY OF VILLAGES MARKET DEVELOPMENT: FOR GENERATING RURAL ECONOMY IN PONOROGO - Indriya Radiyanto; Pawana Nur Indah (UNEJ e-Proceeding, 2017)
The scope of research put emphasis on the rural market development programtargeting the rural economy as a generator in Ponorogo cross - sectional. This research used astructured survey, direct interviews with the respondents using a questionnaire. Number ofVillage Market is a total of 47 (forty seven) Market Village which spread over 18 (eighteen)districts. Physical Condition of the Village Market, is associated with a protective roof fromthe sun or rain, as many as 26 markets (55.32%) are in good condition, a total of 12 markets(25.53%) in the partially damaged and just as much as 9 market (19.15 %) damagedcondition. Perception buyer / village communities with the existence of the village market, asmany as 70 people purchasers (70%) stated often spending to market, as many as 20 peoplewere buyers (20%) stated quite often shopping to the market and there were 10 buyers(10%) said rarely spending to the village market. Perception merchant with the presence ofthe village market, as many as 65 traders (65%) stated that his business in the market hasgood prospects, as many as 30 traders (30%) stated that good business prospects and asmany as five dealers (5%) stated that its business prospects less good. The existence of ruralmarkets are still highly needed by the community (the buyer), especially the communityaround the market, either to meet daily needs, also for sale again or for the productionprocess. Desired institutional traders in the market in Ponorogo, namely the berkelindan withthe aspect of togetherness, security and can help financial difficulties (the capital).